On the Possibility of Crucial Experiments in Biology. (1st September 2017) - Baetu, Tudor
Abstract: The article analyses in detail the Meselson–Stahl experiment, identifying two novel difficulties for the crucial experiment account, namely, the fragility of the experimental results and the fact that the hypotheses under scrutiny were not mutually exclusive. The crucial experiment account is rejected in favour of an experimental-mechanistic account of the historical significance of the experiment, emphasizing that the experiment generated data about the biochemistry of DNA replication that is independent of the testing of the semi-conservative, conservative, and dispersive hypotheses. 1 Introduction 2 The Meselson–Stahl Experiment 3 Some Difficulties for the Crucial Experiment Account 3.1 Additional experiments were required 3.2 Simplicity considerations are unconvincing 3.3 The fragility of the experimental results 3.4 The problematic interpretation of falsifyng results 3.5 Not all possible hypotheses considered or tested 3.6 The tested hypotheses were not mutually exclusive 4 The Historical and Scientific Significance of the Meselson–Stahl Experiment 4.1 The challenge for the crucial experiment account 4.2 A mechanistic perspective on the experiment 4.3 The experimental design and its independence from theoretical speculations 4.4 The advantages of a 'bottom-up' mechanistic account 5 Conclusion